Komunikasi Profetik dalam Mendorong Pembangunan Desa (Studi Kasus Desa Medini Kabupaten Kudus) - Fadhila, Uliya; Sarah Sangadah; Muhammad Fikri Al Qudsy; Intan Nurul Dwi Syifana (Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the role of prophetic communication in guiding community development through humanistic research, liberalism, and transcendence using a case study in Medini Village, Undaan District, Kudus Regency. The research methodology used is ethnography, a qualitative approach that aims to understand social phenomena, through direct observation and participation in the field, using data collection techniques such as document analysis, participant observation, and direct interviews. Research participants consisted of community leaders and village officials. Through this approach, prophetic communication invites the community to actively participate in the development process, strengthens the relationship between the community and the government, and ensures that the needs and aspirations of residents are heard. This study uses Kuntowijoyo’s prophetic social science theory. The core ideas of prophetic social science are humanism (humanity), liberalism (liberation), and transcendence (divinity).